Safewards Impact in Inpatient Mental Health Units in Victoria, Australia: Staff Perspectives - Fletcher, Justine; Hamilton, Bridget; Kinner, Stuart A.; Brophy, Lisa (Frontiers in Psychiatry, 2019)
Introduction: Mental health professionals working in acute inpatient mental health wards are involved in a complex interplay between an espoused commitment by government and organisational policy to be recovery oriented and a persistent culture of risk management and tolerance of restrictive practices. This tension is overlayed on their own professional drive to deliver person-centred care, and the challenging environment of inpatient wards. Safewards is designed to reduce conflict and containment, through the implementation of 10 interventions that serve to improve the relationship between staff and consumers. The aim of the current study was to understand the impact of Safewards from the perspectives of staff. Methods: One hundred and three staff from 14 inpatient mental health wards completed a survey 12 months after the implementation of Safewards. Staff represented four service settings: adolescent, adult and aged acute, and secure extended care units. Results: Quantitative results from the survey indicate that staff believed there to be a reduction in physical and verbal aggression since the introduction of Safewards. Staff were more positive about being part of the ward, and felt safer and more connected with consumers. Qualitative data highlight four key themes regarding the model and interventions: structured and relevant; conflict prevention and reducing restrictive practices; ward culture change; and promotes recovery principles. Discussion: This study found that from the perspective of staff, Safewards contributes to a reduction in conflict events and is an acceptable practice change intervention. Staff perspectives concur with those of consumers regarding an equalising of staff consumer relationships and the promotion of more recovery-oriented care in acute inpatient mental health services.